MENELISIK EKSISTENSI KEBUDAYAAN BALI: KAJIAN PENINGGALAN-PENINGGALAN DI MUSEUM BALI - Noor Amelia Latifah; Sri Rachmawati; Zitni Ilma; Lisa Hayu Triningsih; Ananda Dimaskuri; Hany Nurpratiwi; Ufi Saraswati (Kampus Akademik Publiser, 2024)
The existence of Museum Bali not only stores historical items, but also shows the life and transformation of Balinese society today. With the existence of Museum Bali, we can peek into the lives of Balinese people in the present. Museum Bali is not only a repository of cultural artifacts, but also a center of education and appreciation for the traditions and values passed down by our ancestors. From fine art collections, traditional clothing, to traditional musical instruments, the museum is a bridge that connects the past with the present. The existence of Museum Bali reflects how Balinese society has adapted to the changing times. The Balinese system of life, beliefs, and patterns of behavior can undergo changes as the accelerating waves of globalization can affect them.